If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(2x+12)=6x+14
We move all terms to the left:
3(2x+12)-(6x+14)=0
We multiply parentheses
6x-(6x+14)+36=0
We get rid of parentheses
6x-6x-14+36=0
We add all the numbers together, and all the variables
22!=0
There is no solution for this equation
| 12-6=2x+8 | | M^4-3m^2-4=0 | | 5+3/4x=7/4x-3 | | 2/5x+18=10+6/5x | | x=10=2x-20/x-10 | | x=102x-20/x-10 | | 5+3/8x=11/8x+4 | | 5x2+13x=0 | | 4(2/5x-7)=20 | | -1.5x+2=0.5 | | m^+4m-12=0 | | x=-14-(-10) | | 2/5x-3=4+9/5x | | 9+1/3x=4+4/3x | | 1/2(7x-6)=6x-10= | | |2x+10|=|5x-11| | | (5x+6÷7)-(11x+2÷21)=2.6 | | 0.6x-x=20 | | |4u+8|=4 | | 58(4w+1)/3=-7 | | 8(s-7)=-40 | | (n+5)*5=65 | | 6-2x4=-2 | | 14x+35=7x+84 | | 2x+1=5x+16 | | 4/80=n | | 3x+1=8x-19 | | 4x+1=3x=2 | | 2x+1/2x=0 | | (10-3b)+6b=22 | | 3.75x=4 | | 101/6+x+143/8=361/3-81/3 |